Comparative performance evaluation of smart reversible thermochromic pigment-based cement and polymeric mortars. (15th October 2022) - Ali Sikandar, Muhammad; Ullah, Saif; Umar, Daanyal; Bashir, Muhammad Tariq; Ali, Liaqat; Waseem, Muhammad; Qazi, Azhar
Abstract: Use of thermochromic (TC) materials has demonstrated benefits in reducing the energy demand of buildings. The present study reports the performance comparison of smart reversible thermochromic cement and polymeric mortars. For this purpose, cement, epoxy, and polyester mortars were fabricated with and without thermochromic pigment. After that, the properties such as water absorption, compressive strength, and ultrasonic pulse velocity (UPV) were assessed for all specimens. In addition, analytical characterization, i.e., X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), Energy dispersive X-ray (EDX) analyses on the mortars were performed. The color stability, solar reflectance, and temperature tests on mortars after exposure to control and natural environments for 28 and 180 days, respectively, were also performed. The results revealed that compared with thermochromic cement mortars, the thermochromic polymeric mortars retain their color, solar reflectance, and temperature regulation properties, leading to a lower diminution in the control and natural environment. The SEM analysis suggests that the TC pigment microcapsules were firmly embedded in the polymeric matrix leading to a stable chromatic response of mortars. On the other hand, the harsh alkaline cementitious environment leads to degradation and deterioration in the chromatic response of TC pigment. Furthermore, polymeric thermochromic mortars exhibited higher compressive strength, ultrasonic pulse velocity, and lower water absorption values than cement-based thermochromic mortars. Hence, polymeric mortars are more suitable for fabricating smart thermochromic composites. Highlights: Thermochromic (TC) pigment-based cement and polymeric mortars were fabricated. TC polymeric mortars exhibited higher compressive strength than TC cement mortars. TC polymeric mortars exhibited lower water absorption than TC cement mortars. TC polymeric mortars retained their optical and temperature regulation properties. Analytical characterizations revealed the functionality of TC pigment in mortars.